Turning defenders into defendants : the use of lawfare against environmental activists in Southeast Asia / Agung Wardana. - Wardana, Agung (TEL transnational environmental law, 2026)
This book documents the mobilisation of law to retaliate against, intimidate, and even punish environmental defenders in Southeast Asia. It draws on case studies from Indonesia, Thailand, and the Philippines, which have taken measures to provide legal protection to environmental defenders by adopting anti-SLAPP provisions. Despite these provisions, attacks utilising legal means against environmental defenders have persisted. Environmental activists and local communities defending their livelihoods and the environment against the encroachment of extractive industries and state-backed development projects are turned into defendants before the courts. The book explains 1) the nature of legal attacks on environmental defenders in Southeast Asia, 2) the consequences of these attacks on environmental movements in those countries, and 3) the responses of environmental movements in navigating the existing politico-legal structures to resist these attacks and their strategies to strengthen the protection of environmental defenders in the region.